PENINGKATAN KETERAMPILAN PEGAWAI KECAMATAN GUNUNGTANJUNG KABUPATEN TASIKMALAYA MELALUI PELATIHAN PENULISAN SURAT DINAS - Agustini, Rina (Empowerment : Jurnal Pengabdian Masyarakat, 2018)
The sub-district office is a government institution that uses letter media in delivering information or activities carried out to support government programs. Writing official letters is one of the activities in administration that can help smooth the activities of the administration. Therefore, writing official letters is very important to be understood by all sub-district office employees to support the administrative work process. The purpose of this service activity is to find out the understanding of writing official letters of the Gunungtanjung District Office of Tasikmalaya District and to find out an increase in understanding of writing official letters of the Gunungtanjung District Office in Tasikmalaya District. The implementation of Community Service activities is packaged using a workshop approach. The activity was carried out using the method of lecture, discussion and practice. The achievement of the training activities was the increasingly motivated sub-district office staff to improve their competence and professionalism in writing official letters. The quality of official letters that have been produced by employees of the Gunungtanjung District Office in Tasikmalaya Regency has also increased as explained below. 20 official letters with very good categories, 7 official letters with good categories, and 3 official letters classified as sufficient (score <70). The training activities benefited the participants and were expected to improve the quality of services in the Gunungtanjung District Office in Tasikmalaya Regency. Keywords: official letter, sub-district employee. ABSTRAK Kantor kecamatan merupakan lembaga pemerintah yang menggunakan media surat dalam menyampaikan informasi atau kegiatan-kegiatan yang dilaksanakan guna mendukung program pemerintah. Penulisan surat dinas merupakan salah satu kegiatan dalam administrasi yang dapat membantu kelancaran aktivitas bidang administrasi. Oleh karena itu, penulisan surat dinas sangat penting dipahami oleh semua pegawai kantor kecamatan untuk mendukung proses kerja administrasi. Adapun tujuan dilaksanakannya kegiatan pengabdian ini yaitu untuk mengetahui pemahaman penulisan surat dinas pegawai Kantor Kecamatan Gunungtanjung Kabupaten Tasikmalaya dan untuk mengetahui peningkatan pemahaman penulisan surat dinas pegawai Kantor Kecamatan Gunungtanjung Kabupaten Tasikmalaya. Pelaksanaan kegiatan Pengabdian Pada Masyarakat ini dikemas dengan menggunakan pendekatan workshop. Kegiatan dilakukan menggunakan metode ceramah, diskusi dan latihan. Pencapaian dari kegiatan pelatihan ialah semakin termotivasinya para pegawai kantor kecamatan untuk meningkatkan kompetensi dan profesionalitasnya dalam penulisan surat dinas. Kualitas surat dinas yang telah dihasilkan oleh para pegawai Kantor Kecamatan Gunungtanjung Kabupaten Tasikmalaya juga mengalami peningkatan sebagaimana uraian berikut. 20 surat dinas dengan kategori sangat baik, 7 surat dinas dengan kategori baik, dan 3 surat dinas tergolong katerori cukup (skor < 70). Kegiatan pelatihan dirasakan manfaatnya oleh para peserta dan diharapkan dapat meningkatkan kualitas pelayanan di Kantor Kecamatan Gunungtanjung Kabupaten Tasikmalaya.